Legal and Ethical Validity of the Thesis Jockey Services Agreement - Fathurrahman, Aditya; Mediawati, Noor Fatimah; Abdulovna, Daryna Dzemish (Indonesian Scientific Publication, 2024)
This research examines the validity of thesis jockey service agreements from a legal perspective, focusing on the complexities arising from paid academic work. The study analyzes the legal implications of intellectual property rights, contractual validity, and potential criminal liability under existing regulations. A normative juridical approach is employed, utilizing a statute-based analysis of relevant laws, particularly Law No. 20 of 2003 on the National Education System. The research relies on secondary data sources, including legal texts, court decisions, and scholarly articles. Data collection is conducted through a literature review, and the analysis technique follows qualitative juridical interpretation to assess legal risks and implications. The study identifies key legal concerns, such as intellectual property rights violations, contractual obligations, and the potential for fraud or document forgery. It highlights that payments for thesis writing services may constitute an employment relationship, raising ethical and legal dilemmas. The findings indicate that service providers and clients may face legal consequences, including criminal charges for academic dishonesty and violations of copyright law. The research underscores the legal risks associated with thesis jockey services and emphasizes the need for stricter enforcement of academic integrity policies. The study calls for increased awareness of legal consequences and improved regulatory measures to safeguard educational integrity. This research contributes to the understanding of academic integrity and legal accountability, providing insights for policymakers, educational institutions, and legal practitioners to address the challenges posed by paid thesis writing services.